Decoding Cystic Lesions in Mixed Dentition through Step-by-step Diagnosis - Arushi Sharma; Namita Singh; Winnie Sharma; Mehak Jindal (Wolters Kluwer Medknow Publications, 2024)
Radicular cysts are the most often documented inflammatory cysts in the adult population, although their incidence in children is regarded as unusual. This study presents a 12-year-old female patient, who had an asymptomatic radicular cyst along with a retained and decayed deciduous tooth in the left posterior mandibular area, the cyst. The patient underwent cystic enucleation after a clinical and radiographic evaluation which led to a provisional diagnosis that was corroborated by the histological findings. In this article, the differential diagnosis and treatment of a radicular cyst in a pediatric patient is discussed.